2014
DOI: 10.20525/ijrbs.v3i1.215
|View full text |Cite
|
Sign up to set email alerts
|

Activism: A Strong Predictor of Proactive Environmentally Friendly Buying Behavior in Turkey

Abstract: The market for environmentally friendly products in Turkey is growing, and marketing experts are trying to understand the behavior of the consumers in this market with the help of variables such as demographic factors, information, attitudes, values and life styles. This study analyzes the effects of environmental activism, environmental knowledge and the perceived seriousness of environmental problems on green buying behavior. The study involved 516 Turkish consumers, over eighteen years of age. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…In fact, the latter point has been corroborated in several studies [54][55][56] where a positive relationship between education and PEB was found. Lastly, we found that willingness to sacrifice for the environment, environmental activism, and environmental knowledge are all predictors of PEB, thus in agreement with the study of Ergena et al [57] as they reported similar findings. These findings provide guidance on what interventions are necessary for raising the profile of environmental stewardship amongst citizens in South Africa.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…In fact, the latter point has been corroborated in several studies [54][55][56] where a positive relationship between education and PEB was found. Lastly, we found that willingness to sacrifice for the environment, environmental activism, and environmental knowledge are all predictors of PEB, thus in agreement with the study of Ergena et al [57] as they reported similar findings. These findings provide guidance on what interventions are necessary for raising the profile of environmental stewardship amongst citizens in South Africa.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…This leads to the understanding that people who have this behavioural trait (environmental activists) engage in sustainable fashion consumption. These findings corroborate with the discussions pointed out by Stern (2000) and Ergen et al (2014), that environmental activists mobilize in favour of sustainable behaviour, which involves not only an active role in claims for sustainable practices of organizations, but which can also be reflected in their consumption choices, revealed in this study in terms of the sustainable fashion purchase intention.…”
Section: Discussionsupporting
confidence: 92%
“…The mediation relationship is not as strong as the direct relationship, which may be a result of the perspective that voluntary simplifiers are more individualistic and motivated mainly by egocentric reasons, such as increasing personal time and seeking a healthier and less stressful lifestyle (Sandlin and Walther, 2009; Shaw and Newholm, 2002). As a result, they rarely express their concerns through collective action, unlike activists (Ergen et al , 2014). They possibly choose to change their personal habits as a way to protest against dominant issues, such as the search for more sustainable forms of consumption, like sustainable fashion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations